LEGALITAS ULTRA PETITA DALAM HUKUM ACARA PIDANA PADA PUTUSAN PENGADILAN” - Luis Luis (Jurnal Hukum Adigama, 2021)
Based on Law no. 8 of 1981 concerning the Criminal Procedure Code Article 182 paragraph (4) states that: "The judge's meeting must be based on the indictment and everything that is proven in the examination at the trial." So in this case the judge must decide according to the indictment made by the public prosecutor. But in the case of the Situbondo District Court Decision No. 55/Pid.Sus/2019/PN. The situation did not run according to this, in this case the judge has taken over the role of the public prosecutor because this has been regulated in Article 137 of the Criminal Procedure Code that the public prosecutor has the authority to carry out prosecutions. in this case the judge decides the case outside of what was indicted by the public prosecutor in which case the judge has violated Article 182 paragraph (4) of the Criminal Procedure Code, causing legal problems that need to be investigated further, namely in terms of how the legality of ultra petita in criminal law is Court decision that occurred in Situbondo in decision No. 55/Pid.Sus/2019/PN. Sit. Where the results of the study indicate that the Ultra Petita Decision is because the judge decided outside of what was indicted by the public prosecutor, the judge had deviated from the principles in the Criminal Procedure Code and was contrary to the provisions of Article 137, Article 182 paragraph (4), Article 191 paragraph (1), and Article 193 paragraph (1) of the Criminal Procedure Code.